A fotografia compromissada na espanha: a experiência de Josep Renau nas revistas Orto e Octubre - Barbosa, Carlos Alberto Sampaio [UNESP] (My University, 2013)
The aim of this paper is to investigate the environment in which a proposal for photographs and photo montages created in Spain in the 1930s was developed. To achieve this, the experiences of the Spanish artist Josep Renau and his work in the illustrated magazines Orto and Octubre is examined. There is an attempt to explore how the European experience of proletarian culture and photography was circulated and appropriated by the Spanish cultural universe. I believe that during these years Spain became a production hub and disseminator of political iconography which later spread to Mexico and Latin America.

O objetivo deste artigo é investigar o ambiente no qual se desenvolveu uma proposta de fotografias e fotomontagens compromissadas na Espanha da década de 1930. Para tanto, utiliza como eixo a experiência do artista espanhol Josep Renau e sua atuação em duas revistas ilustradas: Orto e Octubre. Procura-se averiguar como as experiências europeias de uma cultura e fotografias proletárias circularam e foram apropriadas pelo universo cultural espanhol. Acredita-se que, nestes anos, a Espanha se tornou um polo produtor e irradiador de uma iconografia política posteriormente difundida para o México e América Latina.
The committed photography in spain: the experience of Josep Renau in magazines Ortho and Octubre
Keywords: Iconography; Photomontages; Photography; Josep Renau; History of Spain; Iconografia; Fotomontagem; Fotografia; Josep Renau; História da Espanha